The metabolic syndrome - Byrne, Christopher D.; Wild, Sarah H. (Wiley-Blackwell, 2011)
The Metabolic Syndrome is a valuable reference text, covering all aspects of the metabolic syndrome and its constituent diseases including inflammation, oxidation and adipocytokines. This book explains the aetiology, pathogenesis and clinical treatment of all risk factors as well as the relationship with diabetes, non alcoholic fatty liver disease, polycystic ovary syndrome and coronary heart disease. The Metabolic Syndrome has been further improved from the 1st edition that was highly commended in 2006 Annual British Medical Association medical books competition. All chapters from the first.